Secondary Traumatic Stress and Moral Injury in Maternity Care Providers: A Narrative and Exploratory Review - Kendall-Tackett, Kathleen; Beck, Cheryl Tatano (Frontiers in Global Women's Health, 2022)
Introduction A significant percentage of maternity providers have experienced secondary traumatic stress following a traumatic birth. Previous studies identified it as an issue, but this literature review is 5–9 years old. In addition, the construct of moral injury has significantly increased our understanding of secondary trauma for military veterans. In the wake of COVID-19, this construct also applies to healthcare providers. Objectives The present article updates these reviews and compares findings for three groups: labor and delivery nurses, midwives, and obstetricians. The second portion of this review re-examines previously published qualitative research to determine whether moral injury might more accurately describe the experiences of maternity personnel. Methods A comprehensive review of PubMed, Scopus, Web of Science, PsychINFO, and CINAHL was conducted in June 2021 using search terms such as compassion fatigue, secondary trauma, moral injury, labor and delivery, nurses, midwives, and obstetricians. Forty articles were identified, but only 16 focused on secondary trauma or moral injury. Results Secondary trauma is a significant concern affecting at least 25% of maternity staff. However, some countries have very low rates, which correspond to low rates in childbirth-related trauma in mothers. Secondary trauma can lead to several symptoms, including re-experiencing, avoidance, negative changes in mood and cognitions, and hyperarousal, which can cause significant impairment. As a result, many providers decide to leave the field in the wake of a traumatic birth. The incidence of moral injury is unknown, but a re-examination of previously published qualitative data suggests that this construct, generally used to describe combat veterans, does describe some of what providers have reported. Acts of omission, i.e., failure to stop the harmful acts of others had long-term negative effects on labor and delivery nurses, consistent with data from military samples. Two possible mediators were proposed: hierarchical and gendered relationships in hospitals and agency of care. Conclusion The effects of traumatic birth on providers can be severe, including possible psychological sequelae, impaired job performance, and leaving the field. Moral injury expands upon the construct of secondary traumatic stress. This construct better describes the experiences of maternity staff in non-primary roles who witness traumatic births and are often haunted by events that they could not prevent, but often question whether they should have.